Physical and Microbiological Milk Quality of Ettawa Crossbreed Goats In Sempu District, Banyuwangi - Izulhaq, Reza Ikhza; Faradina, Putri Laura; Lestari, Cici; Oktavianti, Dika; Fransia, Nicola Earren; Nuraini, Okta; Nasrulloh, Cheisa Alfii Yudha; Wibawati, Prima Ayu (Jurnal Sain Veteriner, 2025)
This study is to evaluate the quality of milk generated by Ettawa crossbreed goats in Sempu District, Banyuwangi. A total of 30 raw milk samples were collected from Ettawa crossbreed goats, aged 3 to 4 years, across 6 different farms. The organoleptic testing method was employed to evaluate the physical properties of milk samples. Furthermore, tests for specific gravity and pH were conducted. Subsequently, the Total Plate Count (TPC) and Most Probable Number (MPN) methods were utilized to evaluate bacterial presence. The organoleptic evaluations validate that the goat's milk samples adhere to the Indonesian National Standard (SNI) 01-3141-2011 and the Thai Agricultural Standard (TAS) 6006-2008. The mean specific gravity of goat's milk is 1.0316 g/mL, whereas the average pH value is 6.45. The findings indicate that the specific gravity meets the criteria set out by the TAS 6006-2008. The pH value of 6.45 is below the threshold established by TAS. The mean TPC result complies with the Standard Limit SNI, which is under 1x10⁶ CFU/mL. Coliform levels in the milk samples adhere to SNI requirements (below 1 x 10² CFU/mL). The statistics indicate that the milk from the Ettawa crossbreed in Sempu District, Banyuwangi, satisfies the minimal standards set by TAS (2008) and SNI 7388-2009. Despite coliform levels conforming to the average standard, this examination indicated the presence of coliforms in multiple farms. Therefore, it is essential to provide heat treatment or pasteurization to the milk before its ingestion by the general populace.